Recovery colleges: quality and outcomes. Issue 4 (9th November 2015) - Meddings, Sara; McGregor, Jane; Roeg, Waldo; Shepherd, Geoff
Abstract : Purpose: – The purpose of this paper is to review the available evidence regarding the effectiveness and cost effectiveness of Recovery Colleges. To make suggestions for future research. Design/methodology/approach: – Selective review of relevant published studies, including reports in the "grey" literature. Findings: – Despite methodological limitations, it has been consistently found that attendance at Recovery Colleges is perceived to be useful and to help people progress towards their recovery goals. There is some evidence of reductions in service use (and therefore costs). In addition, there is evidence of beneficial effects for peer trainers and possible positive impact on staff attitudes. Research limitations/implications: – The existing research highlights the need for further robust studies, using both qualitative and quantitative methods, to understand better the overall impact of Recovery Colleges and the underlying mechanisms of change. Practical implications: – There is a need for further studies of the relationship between the "key defining features" and outcomes. This means the collection and pooling of systematic, "practice-based" evidence. Social implications: – The introduction of an explicitly recovery educational ("learning") model into mainstream mental health services seems to have a profound effect on reducing the power differences inherent in traditional professional/patient relationships. If this can be replicated across organisations it could facilitate the kind of fundamental cultural change necessary to give back recovery to the people who have always owned it. Originality/value: – The information collected together in this paper is already publicly available, however it is difficult to find. The analysis and interpretation is original.